2000
DOI: 10.1021/ic0002420
|View full text |Cite
|
Sign up to set email alerts
|

Oxo Complexes of Osmium(IV) Formed via Dioxygen Activation. X-ray Structures of [OsX(dcpe)2]PF6 (X = Cl, Br), [OsCl(η2-O2)(dcpe)2]BPh4, and [OsCl(O)(dcpe)2]BPh4 (dcpe = 1,2-Bis(dicyclohexylphosphino)ethane)

Abstract: Dioxygen addition to the 16-electron complexes [OsX(P-P)2]+ (3) gives the dioxygen adducts [OsCl(eta 2-O2)(P-P)2]+ (3), which in turn react with HCl gas to give the novel osmium(IV) oxo complexes trans-[OsX(O)(P-P)2]+ (5) (X = Cl, Br; P-P = 1,2-bis(dicyclohexylphosphino)ethane (dcpe), 1,2-bis(diethylphosphino)ethane (depe), 1,2-bis((2R,5R)-2,5-dimethylphospholano)benzene (Me-duphos)). The complexes [OsX(dcpe)2]+ (X = Cl, Br) (3) are studied by X-ray crystallography and are shown to have a "Y-shaped" coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…[2][3][4][5] In the majority of cases, structurally characterised examples feature bidentate phosphane ligands with bulky substituents, and this has placed limits on the extent to which these systems can be systematically investigated by variation of the phosphane ligands. One approach to extending the family of [ML 4 H] + species is to replace phosphanes by N-heterocyclic carbenes (NHCs).…”
Section: A C H T U N G T R E N N U N G (H 2 -H 2 )H]mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] In the majority of cases, structurally characterised examples feature bidentate phosphane ligands with bulky substituents, and this has placed limits on the extent to which these systems can be systematically investigated by variation of the phosphane ligands. One approach to extending the family of [ML 4 H] + species is to replace phosphanes by N-heterocyclic carbenes (NHCs).…”
Section: A C H T U N G T R E N N U N G (H 2 -H 2 )H]mentioning
confidence: 99%
“…Thus, the Ru (12) and NHC = IMe 4 (13) from reactions performed in pyridine, while the Ru (14) was produced upon reaction of 2 with dioxygen in CD 2 Cl 2 . [5,38] The X-ray crystal structures of these three compounds are provided in the Supporting Information.…”
Section: Reactivity Of 2 and 3 With Omentioning
confidence: 99%
“…A report showed that dioxygen can be activated via formation of an oxo-osmium(IV) π-complex. 36 1-Zn-O 2 is also a type of π-complex. In 1-Zn-O 2 , the lone electron pair of the terminal O atom, rather than the π electron in the oxo-osmium(IV) complex above, 37 of dioxygen donates an electron pair to a zinc d-orbital to form a σ-coordination bond (Figure 4a-I).…”
mentioning
confidence: 99%
“…The 31 P{ 1 H} NMR spectrum of 1 shows a singlet signal at δ = 78.5, which is clearly downfield with respect to that of the free ligand (δ = 55.3 ppm, br), the deshielding (Δδ = δ complex − δ ligand = +23.2) being intermediate to those found in the analogous trans ‐[RuCl 2 {κ 2 ‐ P , P −Ph 2 PN(R)PPh 2 } 2 ] [R = i Pr (Δδ = +27.1); H (Δδ = +18.0)] 7b. The 31 P{ 1 H} NMR spectrum of 2 shows two triplets (A 2 X 2 spin system) at 72.57 and 87.73 ppm ( 2 J P,P′ = 31.1 Hz) indicating that a single diastereoisomer, Δ( S , S ) or Λ( S , S ), is formed 11. These signals can be assigned to the axial (P trans to P) and equatorial (P trans to Cl) phosphorus nuclei, respectively.…”
Section: Resultsmentioning
confidence: 99%